PRELIMINARY REPORT ON THE ASTRONOMICAL SITE AT SAN PEDRO MARTIR BAJA CALIFORNIA MEXICO - MENDOZA, EUGENIO (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1976)
Astronomical and meteorological data that cover the 1968-1971 period indicate that the Observatorio Astronomico de San Pedro Martir, Baja California is one of the best existing sites in the northern hemisphere. We give numerical data for the number of ent
BOL AGRI
Keywords: PRELIMINARY, REPORT, ASTRONOMICAL SITE, SAN PEDRO MARTIR, BAJA CALIFORNIA, MEXICO; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; ASTRONOMIA DE POSICION